Developing an intersectional consciousness and praxis : moving toward antiracist efforts in higher education - McElderry, Jonathan; Hernandez, Stephanie (Emerald Publishing Limited : Information Age Publishing, Inc., 2025)
"Colleges and universities across the country continue to struggle supporting students with marginalized identities, including (but not limited to) gender, race, ethnicity, sexual identity, ability level, socio-economic status, religious identity, and citizenship status. The creation of safe and inclusive learning environments necessitates the adoption of equitable policies and practices (McElderry & Hernandez-Rivera, 2019). Therefore, this book can be used as a tool for practitioners to further support students from marginalized identities at PWIs. Grounded in the NASPA/ACPA Core Competencies, this book allows practitioners to share their knowledge and best practices in how they support students of color across the following functional areas in higher education: Student Learning & Development; Social Justice & Inclusion; Health & Wellbeing; Advising & Supporting; Assessment, Evaluation, & Research; Senior/Executive Leadership"-- Provided by publisher.
Keywords: Discrimination in higher education -- United States -- Prevention.; Minority college students -- Services for -- United States.; Sexual minority college students -- Services for -- United States.; Intersectionality (Sociology); Education -- Schools -- Levels -- Higher.; Higher education, tertiary education.; elektronické knihy; electronic books